Eskom's employees perception on nuclear power in accordance with the IRP 2010 Nuclear Energy Plan - Chutri, Mithun (Department of Electrical Engineering, 2018)
The future role of nuclear power in global sustainable development, and particularly in the development of industrialising countries is contentious; the debate is often highly emotive. The Republic of South Africa's (RSA) progress towards its largest nuclear procurement program is taking place in the midst of changes within the African National Congress (ANC) ruling party, an increase in global demand for uranium and growing energy needs within South Africa. Major nuclear accidents such as Chernobyl or Fukushima have set nuclear power plant security on top of the public agenda. The internalisation of governance through the creation of responsible eco-citizenship is a primary technique to screen perceived risk, which works through the course of public participation. Participation however, must include those that drive the objectives within the nuclear context. Eskom's Koeberg Nuclear Power Station (KNPS) has a workforce of more than 2000 employees. In 2016, the Department of Energy (DOE) had decided that Africa's leading power utility will be the owner operator and procurer of the planned 9.6 Gigawatts (GW) (e) nuclear fleet that is set out in the IRP2010 report. The perceptual impact of this workforce that keeps the country's economic lifeblood moving is often understated, which was the focus of this study. This study had a distinct focus on what Eskom employee's perceptions are with respect to the IRP2010 nuclear new build program. It was limited to the Western Cape Province and included views from divisions that may be involved in the realisation of the nuclear project. It is unique in its context, as very little has been documented on employee perception within RSA's nuclear industry. It is comparative to a public perception survey, which had a distinct focus on nuclear risk. The public's greatest concerns were noted to be corruption, project mismanagement, excessive cost and lack of trust in stakeholders. The outcome of this study discovered similarities with the public perception survey, however here within nuclear safety and compliance to business best practice were greater significant factors. Most respondents had sufficient knowledge and support for RSA's nuclear plans set out in the IRP reports. Dimensions of how perception was created were voted as being heavily dependent on the leadership within the organisation. With this in mind, Eskom employees have indicated that they are more likely to influence the public if they have their leadership's support, and have gone as far as selecting nuclear power over renewable energy to drive towards the country's commitment towards low greenhouse gas (GHG) emissions. So while there may be shades of perceptual similarities between the public and Eskom employees, fundamentally this study revealed that these two bodies do not have the same perception on nuclear power. The study revealed that if Eskom employee's nuclear perception is disregarded and mismanaged, it may delay the realisation of the nuclear new build program in line with IRP 2010 timelines. This is mainly due to the concern of adherence to good corporate governance by Eskom's leadership.